(untitled) (Swiss Medical Weekly, 2021)
AIMS To describe the feasibility and diagnostic accuracy of 18F-FDG positron emission tomography-computed tomography (PET/CT) of the temporal artery compared with temporal artery ultrasound and histology of the temporal artery in patients with suspicion of having giant cell arteritis (GCA). MATERIALS AND METHODS Patients with suspected GCA were included. PET/CT standard uptake value ratios and the compression sign on ultrasound were assessed for the trunk, and parietal and frontal branches of the temporal artery. Temporal artery biopsies were systematically re-assessed, if available. RESULTS In 17/34 patients, GCA was confirmed. Temporal artery PET/CT confirmed vasculitis in 9/17 patients and was negative in all 17 controls. Nineteen of 34 subjects had a temporal artery biopsy, which was positive in 7 patients. Five of these seven were negative in the preceding PET/CT. Ultrasound confirmed vasculitis in 9/17 patients and was negative in 16/17 controls. In 7/17 patients, PET/CT and ultrasound were positive for temporal arteritis. Two patients had positive findings only on temporal artery PET/CT and two patients showed vasculitis only on temporal artery ultrasound. No temporal artery segments <1.4 mm were positive on PET/CT. The parietal branches were PET/CT-positive in two patients only. In contrast, on ultrasound vasculitic findings were equally distributed amongst all branches. Sensitivity and specificity for identification of temporal artery involvement was 53% and 100% for PET/CT, and 53% and 94% for ultrasound, respectively. CONCLUSIONS Assessment of the temporal artery with PET/CT is a valuable extension in the diagnostic workup for GCA. PET/CT and ultrasound have comparable diagnostic accuracy, but differ on a segment and a patient level and may thus be used as complementary tests. PET/CT has a lower sensitivity for the parietal branch than ultrasound and histology.